If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -2 = 3 + x + 5 Reorder the terms: -2 + 5x = 3 + x + 5 Reorder the terms: -2 + 5x = 3 + 5 + x Combine like terms: 3 + 5 = 8 -2 + 5x = 8 + x Solving -2 + 5x = 8 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -2 + 5x + -1x = 8 + x + -1x Combine like terms: 5x + -1x = 4x -2 + 4x = 8 + x + -1x Combine like terms: x + -1x = 0 -2 + 4x = 8 + 0 -2 + 4x = 8 Add '2' to each side of the equation. -2 + 2 + 4x = 8 + 2 Combine like terms: -2 + 2 = 0 0 + 4x = 8 + 2 4x = 8 + 2 Combine like terms: 8 + 2 = 10 4x = 10 Divide each side by '4'. x = 2.5 Simplifying x = 2.5
| 1+33d+20+1+12=38 | | 14+3p=20 | | 2-3(x-7)=-1 | | 1+33d+20-1-12=38 | | -2a+24+8a=4a-6a | | 6z-13-z+3=0 | | 3/4t=-48 | | 12/-4/9 | | 4y+2y=5y-2 | | 2(4x-8)+6(5x+2)=6(4x+9)3 | | 3a^2-8a-24a+64= | | 9+m/=2 | | 6x-9+4x=51 | | -1-5x=-26 | | 5(5y-4)-8y= | | 2x^2-6x-2ax+8+a^2=x-1 | | x^3-37x+84=0 | | 80+60+x+51=180 | | (3x-1)-3(2x+3)+42=2x(-x-5)-(x-1) | | 6x+x-6=6x+4 | | 6w-4+4=-3+3+4 | | 2x-6=5x+18-3(x-4) | | -(w+4)=-8w+9 | | 10x+8-5x-3=-16 | | 200+15x=424 | | -4s^2-11s=-3 | | 3-3x=-27 | | (3p-6)=90 | | 7g-5-3-7g= | | 5x+6=-3+2x+18 | | -3(x-6)=66 | | 5=a/4+8 |